Body on Machine Arm, performance, Exhibited at: Lorne Sculpture Biennale, on the foreshore at Swing Bridge, Lorne, Australia, 26 March 2016 - Stelarc, Stelarc (2016)
The body is an object among other interacting objects. The body performs physical acts and creates relationships between objects, generating meaning and significance. Body on Machine Arm continues the artist’s research into the relationship between human bodies and technology. Self, agency and identity are unsettled and made ambivalent in increasingly liminal zones of operation and interface with machinic entities that move the body in unexpected ways. The performance at the Lorne Sculpture Biennale explored the body as a component of a larger system of machines, presenting a kind of flattened ontology which does not assert the primacy of the human.